Análisis jurídico y funcional del crédito documentario en un entorno digitalizado - Jiménez Jiménez, María Mercedes (Universidad de Sevilla, 2025)
El crédito documentario. también denominado en la literatura jurídica como documentary letter of credit, es un medio de pago, un instrumento de financiación y una garantía. Es una operación bancaria cuyo origen se encuentra en el receptum argentarii del Derecho Romano Clásico. Su desarrollo ha sido paralelo a la evolución de la economía, el comercio y la banca. Desde el siglo XIX, el crédito documentario es una institución de gran importancia en el comercio internacional. Se define como todo acuerdo a través del cual, el ordenante (importador) se obliga frente al beneficiario (exportador) a solicitar la emisión de un crédito documentario a su entidad bancaria o financiera (banco emisor), la cual llevará a cabo el pago, aceptación o negociación del mismo a favor del beneficiario, siempre que éste presente al banco emisor (u otra entidad bancaria o financiera designada) una determinada documentación y dicha entidad bancaria o financiera preste su conformidad. Entre sus rasgos principales podemos resaltar la pluralidad de partes que intervienen en su operativa -inicialmente tripartita-, su naturaleza jurídica compleja o los principios rectores que lo rigen como son los principios de independencia y de estricto cumplimiento. Consecuencia de estas características, el crédito documentario es una figura que ha suscitado múltiples debates doctrinales y jurisprudenciales. La ausencia de Ley que lo regula en gran parte de los Ordenamientos Jurídicos del mundo también ha conllevado su difícil tratamiento. Sin embargo, gracias a la Cámara de Comercio Internacional de París, el crédito documentario es una figura regulada por las Reglas y Usos uniformes relativos a los créditos documentarios (actualmente RUU nº 600 de 2007). Además de ello, los trabajos de UNCITRAL y UNIDROIT han aportado grandes avances en lo que al comercio internacional se refiere y, con ello, a nuestra institución. La naturaleza jurídica de las RUU ha sido también discutida por la doctrina y jurisprudencia. Nueva Lex Mercatoria, usos y costumbres o cláusulas contractuales son algunas de las tesis vertidas. En lo referente a la naturaleza jurídica del crédito documentario, se puede afirmar que estamos ante una pluralidad negocial, lo que implica que el crédito documentario esté conformado por una diversidad de contratos independientes entre sí, pero con un objetivo común. Es necesario determinar la naturaleza jurídica de cada una de las relaciones que lo componen. Diferentes han sido las tesis vertidas sobre cada una de estas relaciones. Sin embargo, las posturas mayoritarias han podido calificar la relación entre importador y exportador (contrato subyacente que, en puridad, no forma parte de la operativa del crédito documentario), la relación entre ordenante y banco emisor (contrato de comisión), la relación entre el beneficiario y banco emisor (promesa unilateral) o la relación entre entidades bancarias o financieras con el banco emisor (contrato de comisión). No es posible, consecuentemente, determinar la naturaleza jurídica del crédito documentario como contrato unitario. Los documentos que ha de presentar el beneficiario para hacer efectivo su derecho de cobro, aceptación negociación del crédito documentario pueden ser los que expresa y voluntariamente dispongan las partes. Sin embargo, las RUU nº 600 establecen los más utilizados en el comercio internacional. Estos son la factura comercial, la póliza de seguro y los documentos de transporte, siendo el conocimiento de embarque el más habitual. El examen de los documentos se rige por los principios rectores dispuestos. En la actualidad, tanto la presentación como el examen de los documentos puede realizarse digitalmente. Aunque no pueda hablarse de un verdadero crédito documentario electrónico, los avances tecnológicos han ayudado a modernizar esta institución. Con ello, no solo se minimizan los altos costes, sino que lo dotan de una agilidad en su operativa muy necesaria en el comercio internacional.

L'application extraterritoriale des sanctions économiques dans le commerce international - Abada-Fasquelle, Marjolaine (Université Paris 1, 2024)
La problématique des sanctions économiques extraterritoriales a pris une ampleur particulière depuis l’amende transactionnelle record versée par BNP Paribas pour violation des programmes de sanctions américains. En effet, avec cette affaire, l’extraterritorialité des sanctions économiques est devenue non seulement un sujet encore plus prégnant de la doctrine juridique, en particulier internationaliste, mais aussi un véritable enjeu économique et politique. Or de nombreuses incertitudes entourent le régime juridique des sanctions économiques extraterritoriales, que ce soit dans l’ordre international ou dans l’ordre interne. Cette étude a pour ambition d’apporter des réponses aux différentes questions soulevées par les sanctions économiques extraterritoriales, en mêlant droit positif et prospectif afin de préciser l’état de l’art, mais aussi d’ouvrir certaines pistes de réflexion. À travers une approche à la fois comparative et pluridisciplinaire, le sujet sera abordé sous deux angles : d’un côté, la licéité de l’application extraterritoriale des sanctions économiques et, de l’autre, l’impact de ces dernières sur le commerce international. Plus concrètement, l’étude repose sur une progression dans l’analyse qui consiste, après avoir défini les concepts, à étudier la licéité des sanctions économiques extraterritoriales, puis à mettre en lumière l’impact d’une telle pratique sur les opérateurs économiques et, enfin, à détailler les différentes solutions qui ont pu être proposées pour contrecarrer cette pratique et les effets qui lui sont associés. Cela étant, l’agression de l’Ukraine par la Russie a considérablement influé sur la teneur des débats. Ainsi, bien que l’UE n’ait pas officiellement changé de position vis-à-vis des sanctions extraterritoriales des États-Unis – qu’elle considère traditionnellement comme illicites au regard du droit international public –, elle a commencé elle-même à recourir à des mesures dont la portée pourrait être apparentée, mutatis mutandis, à de l’extraterritorialité. Dans ce contexte, cette étude entend donc finalement faire la jonction entre la perception des sanctions extraterritoriales ayant prévalu pendant plusieurs décennies et le changement de paradigme qui est en train de s’opérer. The issue of extraterritorial economic sanctions has become a matter of particular importance in the wake of the record settlement fine imposed upon BNP Paribas for violating US sanctions programs. This case has thus highlighted the necessity for further discussion and analysis within international legal doctrine, as the extraterritoriality of economic sanctions has also grown in significance as an economic and political issue. The legal framework of extraterritorial economic sanctions is replete with uncertainty, whether in international or domestic law. This study aims to address the multitude of questions surrounding extraterritorial economic sanctions by combining positive and prospective legal approaches. Hence, it ambitions to clarify the current state of the art while also opening paths of thought. The subject will be addressed through a comparative and multidisciplinary approach, examining two perspectives: firstly, the legality of the extraterritorial application of economic sanctions; secondly, the impact of the latter on international trade. The study is based on a progression in the analysis, which begins with the definition of the relevant concepts. It then examines the legality of extraterritorial economic sanctions, before highlighting the impact of such a practice on economic operators. Finally, it outlines the various solutions that have been submitted to counter this practice and the effects associated with it. However, the Russian aggression against Ukraine has had a considerable influence on the content of the debates. Indeed, although the EU has not formally revised its stance on US extraterritorial sanctions – which it traditionally deems unlawful under public international law – it has itself adopted measures whose scope could be seen as extraterritorial. In this context, this study will establish a connection between the perception of extraterritorial sanctions that prevailed over several decades and the paradigm shift that is currently underway.
Issue: 2024PA01D015
Keywords: Anti-circumvention mechanism; Anti-coercion instrument; Blocking statutes; Droit international public; Economic sanctions; Extraterritoriality; Extraterritorialité; Instrument anti-coercition; International public law; Lois de blocage; Mesures restrictives; Mécanisme anti-contournement; Restricitve measures; Sanctions économiques

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO

El principio de proporcionalidad en el derecho international económico - Reyes Sarmiento, Lina (Université Paris 10, 2021)
Le principe de proportionnalité a été récemment reconnu dans les traités et les accords internationaux du commerce et des investissements avec l’État. Cependant, peu d'études se concentrent sur la nature juridique, le contenu, la portée et les fonctions de ce principe dans le droit économique international. Cette thèse présente une analyse actuelle et détaillée sur ces questions.
Cotutelle avec : Université Autonome de Barcelone
Keywords: Arbitrage international; Arbitraje internacional; Dispute resolution; Droit international économique; International Arbitration; Inversiones; Investissements; Investments; OMC; Principes; Principios; Principles; Proporcionalidad; Proportionality; Proportionnalité; Proportionnalité (droit); Règlement des différends; Solucion de diferencias; WTO

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması - Babayev, Ilgar (İstanbul Ticaret Üniversitesi, 2021)
Uluslararası ticaretin gelişimi ve artması dünyadaki bütün devletler tarafından hedeflenen bir amaçtır. Ancak devletlerin ulusal hukuk sistemleri arasındaki farklar bu gelişim için belirli engeller oluşturmaktadır. Bu engelleri aşmak için uluslararası ticaret hukukunun yeknesaklaştırılması, yani aynı uluslararası hukuki işleme uygulanacak iki veya daha çok ulusal hukuk sisteminin farklı kurallarının bir kuralla değiştirilmesi çare olarak görülmektedir. Bu amaçla şimdiye kadar bir çok çalışmalar yapılmış ve bir çok yeknesaklaştırma aracı ortaya konulmuştur. Uluslararası ticaret hukukunun bel kemiğini oluşturan uluslararası ticari sözleşmeler alanında hazırlanmış olan yeknesaklaştırma araçları ise bu bakımdan özellikle önem taşımaktadır. Hukukun yeknesaklaştırılması alanında çalışmalar sürdürülmekle birlikte bu konuya şüpheyle bakanlar ve yeknesaklaştırmanın kendi amacına ulaşamayacağını düşünenler de mevcuttur. Bu yeknesaklaştırma sürecinde ortaya çıkan bir takım sorunlarla ilgilidir. Ancak özellikle de uluslararası ticaret hukuku alanında yapılan yeknesaklaştırma çalışmalarında elde edilen başarılar umut vaat etmektedir. Uluslararası ticari sözleşmeler hukuku alanında yapılmış olan ayrı ayrı yeknesaklaştırma çalışmaları ile ilgili araştırmalar mevcut olsa da, konuyu daha kapsamlı bir şekilde ele alan ve meseleye daha geniş bir perspektiften bakan araştırmaların eksik olduğunu görmekteyiz. Özellikle de Türkiye'de bu tür araştırmalarda bir boşluğun mevcut olduğu hissedilmektedir. Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması amacıyla ortaya konulmuş çalışmaların ve hazırlanmış olan araçların daha kapsamlı bir şekilde araştırılması, onların sağladığı faydaları göstermek, bu alanda ortaya çıkan sorunları belirlemek ve gerekli çözüm önerileri sunmak açısından önem arz etmektedir. Bütün bunları dikkate alarak biz bu araştırmamızda uluslararası ticaret hukukunun yeknesaklaştırılması kavramını, onun önemini ve sağladığı avantajları, yeknesaklaştırmanın gerçekleştirilmesi yöntemlerini, uluslararası ticaret hukukunun yeknesaklaştırılması alanında çalışmalar yapan ve bu sürece katkıda bulunan uluslararası kurumları, uluslararası ticari sözleşmeler alanında yapılmış olan ve şu an yapılmakta olan çalışmaları, bu konuyla ilgili ortaya çıkan sorunları ve bu sorunların ortadan kaldırılması için sunulan çözüm önerilerini incelemeye çalıştık. [...] The development and growth of international trade is an aim targeted by all states in the world. However, the differences between the national legal systems of states pose certain obstacles to this development. To overcome these obstacles, the unification of the international commercial law is considered a remedy, that is, changing the different rules of two or more national legal systems to be applied to the same international legal process with one rule. For this purpose, so far many studies have been done and many unification instruments have been introduced. The unification instruments prepared in the field of the international commercial contracts, which form the backbone of international commercial law, are particularly important in this regard. Although studies on the unification of the law continues, there are also those who are skeptical about this issue and those who think that it cannot achieve its own goal. It concerns a number of problems that arise in the process of unification. However, the successes achieved in the unification studies especially in the field of international commercial law promise hope. Although there are researches on individual unification studies in the field of international commercial contracts law, we see that there is a lack of research that covers the issue more extensively and looks at the issue from a wider perspecitve. Especially, a vacancy in this kind of research is available in Turkey. It is important to investigate the studies and the instruments that have been prepared for the purpose of the unification of the international commercial contracts law, to show their benefits, to identify the problems that arise in this field and to offer necessary solutions. Considering all these, in this research, we tried to examine the concept of the unification of the international commercial law, its importance and advantages, the methods of realization of unification, the international institutions that work in the field of the unification of the international commercial law and contribute to this process, the problems that arise about this issue and the proposed solutions to eliminate these problems.
Keywords: Hukukun Yeknesaklaştırılması; International Commercial Contracts Law; International Commercial Law; International commercial contracts; Lex Mercatoria; Uluslararası Ticaret Hukuku; Uluslararası Ticari Sözleşmeler; Uluslararası Ticari Sözleşmeler Hukuku; Unification Instruments; Unification of Law; Yeknesaklaştırma Araçları

Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch University, 2020)
How do members hold their own trade unions accountable in South Africa? What legal mechanisms, if any, are available to assist union members in receiving adequate representation and service from their unions? This study approaches these questions through a comparative and historical examination of the regulation of the union member relationship in the UK, USA and the RSA. The study commences with an examination of what unions do, how they function and what benefits potentially accrue to their members, while the role played by unions in utilising collectivisation to offset the bargaining power of employers is demonstrated. The need for organised labour, by society in general, but South Africa specifically, is brought into sharp relief. This is, however, offset by the examination of 25 constitutions of broadly representative South African trade unions, where the lack of proper regulation of the union-member relationship is brought to the fore. This already means the common law and current judicial approach that is so reliant on the interpretation and implementation of trade union constitutions to address union-member disputes is unsuitable, certainly in those instances where the constitution is either silent or ambiguous, or where the nature of the relationship between the union and its member(s) mimics that of the constantly present imbalance of power and influence between employers and employees. The comparative examination of union accountability is undertaken against the backdrop of the common historical phases of proscription, acknowledgement/assimilation, and readjustment of and towards trade unions. The historical and contemporary regulation of the union-member relationship in South Africa is examined in the same way. The study demonstrates that purely statutory regulation of the union member relationship by means of punitive provisions and inter-union self-regulation measures are not feasible. A series of possible legal mechanisms – that draw from the comparative examination – are suggested, even though they are to be utilised in a collective (rather than individual) way. Even these suggestions, however, are subject to the challenges of cost-effectiveness, accessibility and efficiency of enforcement by (the) average union member(s). Three proposals are made to foster improved union member accountability: Firstly, the use of section 103A of the LRA by the Registrar so as to place unions that meet the appropriate criteria under administration, in order to restore accountable functioning and elevate the interests of the member(s) over that of the officials of the union; secondly, the introduction of a duty of fair representation – to be administered by the CCMA – to hold both union and employer accountable to members, and; thirdly, in conjunction with the first two proposals, the use of a package of further measures (and an associated information campaign), such as bolstering the financial/institutional capacity of the Registrar’s office, compelling the inclusion of accountability clauses within union constitutions, and minor amendments to the LRA with regard to balloting, reporting/transparency (and the enforcement thereof). If implemented, the expected outcomes are improved labour relations, increased accountability and professionalisation of trade union administration, a realignment of the employer-union divide and elevating the awareness of union member rights and concomitant obligations on trade unions – all of which are of critical importance in South Africa’s post-Marikana society.
URI: http://hdl.handle.net/10019.1/109343
Keywords: Labor union members; South Africa; Trade union accountability; Union security

La non-conformité dans la vente commerciale internationale - Chebbi, Ali-Slah (Université de Carthage, 2020)
La vente commerciale internationale est considérée par tous comme l'épicentre de la mondialisation. Contrat synallagmatique par excellence, elle crée à l'encontre des parties des obligations réciproques. L'une de ces obligations est sans conteste l'obligation de conformité. Contrairement au droit interne qui continue de traiter le sujet à travers une panoplie d'actions qui varient selon l'angle d'attaque de la victime, le droit uniforme issu de la Convention de Vienne du 11 avril 1980 ramène l'ensemble des actions en deux grandes catégories régies soit par les dispositions de l'article 35 CVIM en ce qui concerne la non conformité matérielle, soit par les dispositions des articles 41 et 42 CVIM en ce qui concerne la non conformité juridique. Cette approche unitaire est la pierre angulaire de cette nouvelle édification normative. Sa visée principale consiste au premier abord à éluder les disparités normatives, pierre d'achoppement pour les échanges commerciaux internationaux.
Keywords: Conformité; Eviction; Intellectual property; Propriedade intelectual; Propriété intellectuelle; Qualité; Quantité; Vente internationale

La corruption et le droit du commerce international - Baro, Gné (Bourgogne Franche-Comté, 2020)
La corruption est une pratique qui freine le développement et peut toucher diverses activités, notamment les activités économiques internationales. Elle porte atteinte au bon fonctionnement du commerce international, nécessitant de lutter contre elle.Cette étude vise à mettre en évidence l’existence d’un cadre juridique anticorruption posé par le droit du commerce international qui est à l’épreuve de la lutte contre cette pratique. Ce cadre juridique anticorruption se matérialise par l’existence d’outils pouvant être rangés en deux catégories : les outils appartenant au corpus des règles du commerce international et des outils complémentaires apportés par d’autres règles de droit très largement connectées au droit du commerce international, tels que l’arbitrage international et le droit des investissements internationaux.Ces outils ne suffisent cependant pas à eux seuls à venir à bout de la corruption. Ils nécessitent un renforcement de la lutte contre la corruption. À cet effet, cette étude montrera que les outils principaux et complémentaires du commerce international sont complétés par des actions des acteurs du commerce international : acteurs privés ou publics. Corruption is a practice that hinders development and can affect various activities, including international economic activities. It undermines the proper functioning of international trade requiring the need to fight against itThis study aims to highlight the existence of an anti-corruption legal framework implemented by international trade law which resists to corruption fight. This anti-corruption legal framework is materialized by the existence of tools that can be classified into two categories: tools belonging to the corpus of international trade rules and complementary tools provided by other legal rules very widely connected to international trade law, such as international arbitration and international investment law.However, these tools alone are not enough to overcome corruption. They require a strengthening of the fight against corruption. To this end, this study will show that the main and complementary tools of international trade are complemented by actions of international trade actors : private or public actors.
Keywords: Commerce illicite; Commerce international; Corruption; Droit commercial (droit international); Droit du commerce international; Illicit trade; International trade law; Lutte contre la corruption

Le système généralisé des préférences à l'épreuve de l'Organisation mondiale du commerce - Diouf, Didier François Diégane (Université Cheikh Anta Diop, 2020)
Keywords: Commerce (libéralisation graduelle); OMC; Principe de non discrimination; Principe de réciprocité; Préférence tarifaire

L'Opportunité de la réglementation des contrats de joint-venture en droit OHADA : au regard des droits français, québécois et belge - Diop, Rokhaya (Université Cheikh Anta Diop, 2020)
Keywords: Contrat (réglementation); Droit OHADA; Droit belge; Droit français; Droit québécois; Joint-venture

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
https://ora.ox.ac.uk/objects/uuid:c2dd717f-e53b-4ab6-b848-c089b70adec2
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation